EFEK PROPOLIS CAIR Trigona spp. TERHADAP RESPONS IMUN TIKUS Sprague Dawley YANG DIINFEKSI Sthapylococcus aureus - Kalsum, Nurbani; Sulaeman, Ahmad; Setiawan, Budi; Wibawan, I Wayan Teguh (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2017)
This study aimed to evaluate the effect of liquid propolis of Trigona spp. on the immunological parameters in mice infected with Sthapylococcus aureus. The effects of propolis were analyzed using the macrophage activity as determined by the phagocytic activity and by the production of nitric oxide (NO) in Sprague Dawley rat peritoneal macrophages and the production of antibodies. The results showed that the liquid propolis produces (a) an increase in the phagocytic index, (b) a significant increase in NO production, and (c) an increase over the production of IgG antibodies. This study indicates that the ethanolic extract of propolis of Trigona spp. is able to activate macrophages, promote the production of No and antibodies. The combination of these results suggests that this extract has an immunomodulatory effect and can boost the immune responsse.